Wir sind nicht auf der Welt, um zu Schweigen eine Einleitung in die Rhetorik - Kopperschmidt, Josef 1937- (De Gruyter Mouton, 2018)
"This somewhat unconventional "introduction to rhetoric" does not engage in a historical or systematic survey. Rather, it explores the specific substantive concern of rhetoric: how does persuasive speech help to achieve cooperation based on understanding? In light of this question, the author describes the current status of rhetoric as a modern principle for establishing validity that is based on persuasion"--
1806
Keywords: Rhétorique; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; LANGUAGE ARTS & DISCIPLINES; Persuasion (Rhetoric); PHILOSOPHY; Rhetoric; Rhetorik; Electronic books